Correction: Anomalous and heterogeneous DNA transport in biomimetic cytoskeleton networks. Issue 28 (8th July 2020) - Garamella, Jonathan; Regan, Kathryn; Aguirre, Gina; McGorty, Ryan J.; Robertson-Anderson, Rae M.
Abstract : Correction for 'Anomalous and heterogeneous DNA transport in biomimetic cytoskeleton networks' by Jonathan Garamella et al., Soft Matter, 2020, DOI: ; 10.1039/d0sm00544d .